Maternal fish-oil supplementation reduces presenilin 1 level and the amyloid-beta burden in adult 5xFAD offspring without major changes in brain fatty acids - Milanović, Desanka J.; Perović, Milka M.; Petrović, Snježana B.; Todorović, Smilja T.; Prvulović, Milica R.; Vukojević, Anđela P.; Mladenović, Aleksandra N. (Archives of Biological Sciences, 2024)
Paper description: Early diagnosis and treatment of Alzheimer’s disease (AD) are critical for delaying its progression. The 5×FAD (familial AD) mice model develops amyloid pathology very early limiting the window for nutritional intervention. Maternal supplementation with omega-3-reach fish oil until weaning reduces amyloid burden in adult offspring. Early and sufficient omega-3 dietary intervention can enhance brain resilience to AD-related pathology. Abstract: Omega-3 fatty acid interventions show potential benefits in Alzheimer’s disease (AD) when initiated during its early stages. This study investigated whether maternal diet supplemented with omega-3-rich fish oil (FO) could delay or reduce amyloid beta (Aβ) formation, a key feature of AD, in 5xFAD transgenic offspring. Dams received FO during mating, pregnancy, and lactation. Brain tissues from female offspring were collected at 2 and 6 months of age. The findings indicated a shift in amyloid precursor protein processing, evidenced by increased soluble amyloid precursor protein α (sAPPα) levels, suggesting a transition from amyloidogenic to non-amyloidogenic pathway. FO influenced the expression of presenilin 1 and 2 but did not impact Aβ levels in 2-month-old mice. However, FO reduced the Aβ burden in the brains of 6-month-old animals. Lipidomic analysis revealed that 5xFAD mice have unimpaired omega-3 acquisition during gestation and lactation in comparison to non-transgenic littermates. However, a response to FO supplementation was found in non-transgenic offspring, indicating that alterations in brain lipids are not the primary mechanism of FO-induced Ab decline in 5xFAD. In conclusion, FO did not prevent or delay amyloid pathology in genetically predisposed animals but did mitigate its progression, suggesting mechanisms that warrant further investigation.